The effect of child-related benefits on child poverty and deprivation in Ireland - Doorley, Karina; Sándorová, Simona; Maître, Bertrand (ESRI, 2025)
Child poverty is of growing concern in Ireland and internationally due to the growing body of evidence on the detrimental effects of childhood socio-economic disadvantage on children, both in the short term and in the long term through loss of education, earnings and health. In Ireland, child poverty has been typically higher than that of other groups of the population over the last few years by many metrics. There are a number of ways that policy can tackle child poverty. One such way is increasing the earnings of families with children by reducing barriers to work. Another way is reform to the tax-benefit system, including in-kind benefits, in a manner that targets families with children. This research is concerned with the latter and investigates the effect on child poverty of the existing tax-benefit system, accounting for many in-kind benefits; analysis includes consideration of the At Risk of Poverty rate, the deprivation rate and the consistent poverty rate. Using the microsimulation model, SWITCH, and accounting for in-kind child benefits, we simulate the child AROP rate for 2025 to be 13.9 per cent, the child material deprivation rate to be 19.5 per cent and the child consistent poverty rate to be 5.6 per cent. We estimate that, in the absence of child-contingent benefits, child poverty rates would be considerably higher. Child-contingent in-cash benefits reduce the child AROP rate by 10 percentage points, the child material deprivation rate by 3.2 percentage points and the child consistent poverty rate by 6.7 percentage points. We estimate that in-kind child-contingent benefits also reduce child poverty, albeit by a more modest magnitude. In the absence of in-kind child-contingent benefits, the child AROP rate would be 1.5 percentage points higher, the child material deprivation rate would be 0.6 percentage points higher, and the child consistent poverty rate would be 1 percentage point higher. Using SWITCH, the ESRI’s tax-benefit model, we also simulate some reforms to the tax-benefit system that could further reduce child poverty. These reforms include increases to the Working Families Payment, to Child Support Payments and to Child Benefit, as well as the introduction of a means-tested second tier of Child Benefit. We find that a second tier of Child Benefit would be the most cost effective of these reforms at tackling child poverty, reducing the child AROP rate by 4.6 percentage points, the child material deprivation rate by 0.7 percentage points and the child consistent poverty rate by 2.1 percentage points.